2007
DOI: 10.1002/chem.200700560
|View full text |Cite
|
Sign up to set email alerts
|

Rational Tuning of Melting Entropies for Designing Luminescent Lanthanide‐Containing Thermotropic Liquid Crystals at Room Temperature

Abstract: The connection of twelve peripheral and divergent dodecyloxy chains to a central tridentate aromatic binding unit provides the dodecacatenar ligand L11, for which room-temperature mesomorphism is detected. An enthalpically unbalanced large melting entropy (DeltaSmL11=226 J mol(-1) K(-1)) results from the programmed microsegregation induced in the crystalline phase, a phenomenon which is maintained in the associated lanthanide complexes [Ln(L11)(NO3)3] and [Ln(L11)(CF3CO2)3]2. Low-temperature melting processes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 83 publications
2
35
0
Order By: Relevance
“…8b). 32 When subjected to CFED analysis ( Fig. 9), unusually small absolute cohesive entropy densities are computed in the solid state 0.11 r |S CFED | = (qCFED/qT) P r 0.13 J K À1 cm 3 (Fig.…”
Section: Compoundsmentioning
confidence: 99%
“…8b). 32 When subjected to CFED analysis ( Fig. 9), unusually small absolute cohesive entropy densities are computed in the solid state 0.11 r |S CFED | = (qCFED/qT) P r 0.13 J K À1 cm 3 (Fig.…”
Section: Compoundsmentioning
confidence: 99%
“…It is found that shows aC ol h phase as evidenced by the observation of both a ( 10) and (11) reflection, with evidence for aE u···Eu correlation at 7 and as tacking period of 3.6 . The observation of the stacking period is interesting in comparison to some of the observations above as the ligand here contains the fused C 5 rings and the metal bears the three bulky k 2 -nitrato ligands, which would imply some sort of backto-back arrangement of the complexes in the mesophase.…”
Section: Eu III and Dy Iii Complexesmentioning
confidence: 99%
“…Twor epresentative zinc(II)-terpyridine complexes with hexadecyl chains werec hosen for preliminary photophysical studies, one with (10)(11)(12)(13)(14)(15)(16) and one without (11)(12)(13)(14)(15)(16) af used cyclopentene ring. Absorption and emission studies were carried out in solvents of varying polarity and data are collected in Ta ble 4.…”
Section: Zinc(ii) Complexesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, a substantial amount of research has been devoted to design luminescent liquid crystals to obtain the materials that combine the properties of liquid crystals and rare earth complexes . Most examples of lanthanidomesogens are smectic liquid crystals, which mimicked the disk‐like or rod‐like shape of the conventional organic liquid crystals and some examples of lyotropic lanthanidomesogens have also been reported . However, the high transition temperatures, unworkability, and low thermal stability are major drawbacks that hamper the application of the physical properties of these materials.…”
Section: Introductionmentioning
confidence: 99%